Lower tourniquet cuff pressure reduces postoperative thigh pain in obese patients undergoing total knee arthroplasty - Png, Wenxian; Lee, Wuchean; Tan, Mann Hong (International Journal of Research in Orthopaedics, 2019)
Background: The use of high tourniquet pressures in obese patients undergoing total knee arthroplasty increases the risk of postoperative thromboembolic events and skin complications. Measurement of limb occlusion pressure (LOP) before surgery may lead to the use of lower tourniquet cuff pressure during surgery and thereby reduce the risk of postoperative pain and complications. Methods: Eighty-six obese patients scheduled for total knee arthroplasty were randomized to a control group (n=43) with tourniquet pressures at 300 mmHg or the LOP group (n=43) where a recommended tourniquet pressure was determined based on the patient’s limb occlusion pressure. The primary outcome measure was postoperative thigh pain; the secondary outcome measures were the quality of bloodless field, postoperative drop in haemoglobin, postoperative complications and Oxford knee scores. Results: The tourniquet cuff pressure was significantly lower in the LOP group than in the control group (p<0.001). Patients in the LOP group showed significantly lower postoperative thigh pain scores till postoperative day 3. Our study did not show any difference in intraoperative quality of bloodless field (p<0.103), postoperative complications and Oxford knee scores (p<0.775) at six months after surgery. Conclusions: Our results show that the use of limb occlusion pressure method results in decreased postoperative thigh pain without reducing the quality of the bloodless field. We believe that this method in tourniquet application is safe and beneficial for the subset of obese patients undergoing total knee arthroplasty.